High Tariffs, High Stakes: The Policy Drivers Behind Firm-Level Adoption of Green Technologies - Samuel Rosenow; Alvaro Espitia; Ana Margarida Fernandes (CESifo GmbH, 2025)
Addressing climate change requires green technology deployment. This paper uses firm-level import data in 35 emerging markets to examine how trade policies affect firms' imports of products associated with solar, wind power, and electric vehicle value chains. Panel estimates show a particularly negative effect of tariffs on green value chain imports compared to average imports, especially in solar and downstream segments. This effect is pervasive from import values and quantities to import probabilities, with undiversified firms most affected. Import regulations have smaller, varied impacts. Emerging markets should avoid protectionist policies, as local firms depend on imports to adopt green technologies.
Keywords: F13; F14; L11; O19; 330; imports; green value chains; trade policy; tariffs; non-tariff measures; firm-level imports; decarbonization value chains; green technology adoption; trade and environment; green technologies